Anodic Aluminum Oxide-Based Chemi-Capacitive Sensor for Ethanol Gas - Gi-Hwan Lim; In-Yea Kim; Ji-Young Park; Yong-Ho Choa; Jae-Hong Lim (Nanomaterials, 2023)
Alcohol ingested by humans can be analyzed via breath tests; however, approximately 1% can be excreted via the skin. In this paper, we present a capacitive sensor using hydrophobically treated anodic aluminum oxide (AAO) capable of detecting alcohol excreted through the epidermis. The degree of hydrophobicity based on the duration of exposure to 3-aminopropyltriethoxysilane vapor comprising a small number of Si–NH2 functional groups on the AAO surface was confirmed and the optimal exposure time was confirmed to be 60 min. The hydrophobized AAO showed a 4.8% reduction in sensitivity to moisture. Simultaneously, the sensitivity of the sensor to ethanol decreased by only 12%. Lastly, the fabricated sensor was successfully operated by attaching it to an ankle-type breathalyzer.